Sri Lanka's Middle Path to Sustainable Development in the 21st Century - Sri Lanka's Middle Path to Sustainable Development in the 21st Century (Sri lannka ministry of enviroment and natural resources, 2002)
ministry of enviroment and natural resources August 2002
Keywords: sustainable development